2008
DOI: 10.1115/1.2900728
|View full text |Cite
|
Sign up to set email alerts
|

Method and Detailed Analysis of Individual Hydrocarbon Species From Diesel Combustion Modes and Diesel Oxidation Catalyst

Abstract: An undiluted exhaust hydrocarbon (HC) speciation method, using flame ionization detector gas chromatographs, is developed to investigate HC species from conventional and low-temperature premixed charge compression ignition (PCI) combustion pre- and postdiesel oxidation catalyst (DOC) exhaust. This paper expands on previously reported work by describing in detail the method and effectiveness of undiluted diesel exhaust speciation and providing a more detailed analysis of individual HC species for conventional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Similar fractions (4−22%) have been reported previously when sampling exhaust using Tenax adsorbents. 23,3336 …”
Section: Resultsmentioning
confidence: 99%
“…Similar fractions (4−22%) have been reported previously when sampling exhaust using Tenax adsorbents. 23,3336 …”
Section: Resultsmentioning
confidence: 99%
“…Higher premixedness of the fuel-air charge and lower combustion temperature of PCI (compared to conventional combustion) cause a different oxidation path of fuel during combustion, which produces higher CO and unburned HC emissions as well as a higher portion of partially oxidized fuel, such as alkenes, alkynes, and aldehydes, especially at low load conditions (Dec et al, 2002;Wagner et al, 2004;Sluder et al, 2004;Lewis et al, 2005;Bohac et al, 2006;Han et al, 2008). Moreover, the aspect of post-flame oxidation that a lot of SI combustion studies have reported on (Kaiser and Siegl, 1994;Bohac et al, 2004) may provide a better understanding of PCI combustion because PCI has a relatively higher expansion gas temperature due to the later fuel injection timing (compared to conventional combustion) and available oxygen during expansion.…”
Section: Introductionmentioning
confidence: 97%
“…If a C 9 -C 19 HC is detected in the exhaust but not in the fuel, it is partially oxidized fuel; if a C 9 -C 19 HC is detected in the exhaust and in the fuel, it is considered to be unburned fuel. A more detailed description of the engine, GC set-ups, and test fuel is provided by (Bohac et al, 2006;Han et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2 used in the engine exhaust studies were measured by evaporating 5 µL h −1 of whole fuel into 20 slpm of dry nitrogen at an injection manifold temperature of 60 • C. The PTR-MS sampled directly from this flow, bypassing the thermal desorption sampler and water trap. Gasoline is mostly comprised of hydrocarbons in the C 4 to C 10 range while diesel fuel consists of C 8 to C 25 hydrocarbons (Han et al, 2008;Schauer et al, 1999;Lough et al, 2005;Gentner et al, 2012;Wang et al, 2005). Exhaust is a more complex mixture that contains fuel hydrocarbons plus oxygenated compounds such as aldehydes and ketones, and other hydrocarbons such as alkenes, acetylene, and pyrogenic compounds (Schauer et al, 1999(Schauer et al, , 2002.…”
Section: Diesel and Gasoline Fuel Mass Spectramentioning
confidence: 99%
“…IVOCs are defined as having a saturation vapor pressure between 1.33 × 10 −4 and 1.33 × 10 −1 hPa (10 −4 and 10 −1 Torr) at 25 • C (Robinson et al, 2007;Presto et al, 2009). For the n-alkanes this vapor pressure range corresponds to dodecane (C 12 ) through to octadecane (C 18 ) and compounds within this vapor pressure range comprise a large fraction of diesel fuel and exhaust (Han et al, 2008;Schauer et al, 1999;Siegl et al, 1999;Gentner et al, 2012). Laboratory tests have shown significant SOA formation from long chain n-alkanes, branched alkanes, and cyclic alkanes found in diesel engine exhaust (Lim and Ziemann, 2005;Jordan et al, 2008;Samy and Zielinska, 2009;Tkacik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%